Banking on African values - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Combining African tradition with modern banking management: that is the challenge that Community Banks of Growth better known by their French acronym MC2 (Mutuelles Communautaires de Croissance) have taken on and won in Cameroon...